2020
DOI: 10.3390/ijerph17114044
|View full text |Cite
|
Sign up to set email alerts
|

Examining Body Appreciation and Disordered Eating In Adolescents of Different Sports Practice: Cross-Sectional Study

Abstract: This cross-sectional study aimed to examine the associations between body appreciation, body functionality and disordered eating in a large adolescent sample of different levels and types of sports practice. Method: The sample consisted of 1412 adolescents (59.8% were girls). The ages ranged from 15 to 18 years old, with a mean age of 16.9 (SD = 0.5) for girls and 17.0 (SD = 0.4) for boys. Participants completed an anonymous questionnaire assessing the nature of sports participation, body appreciation, body fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
5
12
0
Order By: Relevance
“…The finding that female exercise science students reported a stronger body appreciation compared to reference students, supports similar differences found between adolescent students participating in leisure and competitive sports compared to non-participants [28]. Our results indicate that even though female exercise science students are exposed to a highly body-oriented environment and bodily capital, and report high levels of BAP, they also report characteristics that might protect their body image.…”
Section: Body Appreciationsupporting
confidence: 84%
“…The finding that female exercise science students reported a stronger body appreciation compared to reference students, supports similar differences found between adolescent students participating in leisure and competitive sports compared to non-participants [28]. Our results indicate that even though female exercise science students are exposed to a highly body-oriented environment and bodily capital, and report high levels of BAP, they also report characteristics that might protect their body image.…”
Section: Body Appreciationsupporting
confidence: 84%
“…This pilot study adds to the knowledge that it is important to test various fitness activities and sports with specially trained fitness instructors or coaches to understand the impact of a wide variety of sports and physical activities on the development of positive body image in women. Studies in belly dancers, athletes and various sports involving adolescents showed the greater positive body image compared physical activity not involved students [54][55][56]. However, the present experimental study adds to the collected knowledge to understand the direction of these associations.…”
Section: Discussionmentioning
confidence: 68%
“…No protective effect of greater satisfaction with body areas was observed in interactions between men's sports participation, BICs, and DE, suggesting that it is important to implement general strategies to decrease BIC's in sport participating men preventing DE in sport. However, in the present study, we did not assess positive body image, i.e., body appreciation that might be a stronger mediator between BICs and DE in exercising men (Jankauskiene, Baceviciene, & Trinkuniene, 2020;Tylka & Wood-Barcalow, 2015). Future studies should test this issue.…”
Section: Discussionmentioning
confidence: 79%